Embedding Feynman integral (Calabi-Yau) geometries in weighted projective space - Jacob L. Bourjaily; Andrew J. McLeod; Cristian Vergu; Matthias Volk; Matt von Hippel; Matthias Wilhelm (Journal of High Energy Physics)
Abstract It has recently been demonstrated that Feynman integrals relevant to a wide range of perturbative quantum field theories involve periods of Calabi-Yau manifolds of arbitrarily large dimension. While the number of Calabi-Yau manifolds of dimension three or higher is considerable (if not infinite), those relevant to most known examples come from a very simple class: degree-2k hypersurfaces in k-dimensional weighted projective space WP1,...,1,k . In this work, we describe some of the basic properties of these spaces and identify additional examples of Feynman integrals that give rise to hypersurfaces of this type. Details of these examples at three loops and of illustrations of open questions at four loops are included as supplementary material to this work.